Enacting a ‘Curriculum of Life’: Mindfulness and Complexity Thinking in the Classroom - Park, Sean Roswell (Paideusis, 2007)
This paper advances Portelli and Vibert’s (2001) concept of a ‘curriculum of life’ as a central organizing concept in education. A curriculum of life, defined as a “curriculum that is grounded in the immediate daily world of students as well as in the larger social, political contexts of their lives” (Portelli & Vibert, 2001, p. 63) is, de facto, at the centre of student learning. I argue that teachers can engage with this immediate daily world and enact a curriculum of life by practicing mindfulness and complexity thinking as ways of valuing relationships and engagement. Complexity thinking in education, which draws upon themes of emergence, self-organization and non-linearity, leads us to a relational ethics that compels educators to take mindful responsibility for how our actions and responses affect the world.